Improvement Teacher Skills in Archiving Letters through Mentoring E-Archive Learning Media - Triesninda Pahlevi; Siti Sri Wulandari; Bambang Suratman; Meylia Elizabeth Ranu (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
Abstract Curriculum years 2013 on administration program offices, there are competence Archive electronically (e-filing). Capaiannya very clear, that it now required the management of electronic archives. Electronic media in the management of the archives will be obtained benefits of speed, convenience and cost-efficient. The intent here is to speed through the use of electronic media in the management of the archives.  The results of the activities of the training and mentoring of the learning model of e-filing is the average of the results of the respondents stating that 92% of the material provided in this training is very important and as much as 90% of the e-filing training participants hope can apply innovation in learning in a class of one e-filing into a medium of instruction.Keyword: e-filing, pedagogy teacher, excellent service